'Don't cross the line, you're a researcher and not an educator': Incorporating indigenous researchers' moral perspectives to improve ethical protocols in health research. (December 2022) - Watson, Sharon
Abstract: Given that researchers from North America and Europe author most global scientific publications, indigenous frontline researcher perspectives are rarely incorporated in the general research enterprise and ethics. Addressing this shortcoming, we analyzed a subset of data from a larger study. We present results from semi-structured in-depth ethnographic interviews with nine indigenous research assistants (RAs) conducted in Southern Africa four years after implementing a national HIV/AIDS study collaboratively implemented by national, U.S., and European-based stakeholders. The aim is to elucidate how these frontline researchers understand and interpret the task of maintaining their role as researchers and when they felt it more appropriate to cross to prevention educator or interventionist. The obtained results demonstrate how practices intended to protect participants and produce minimally biased ethical data create a conflict for frontline researchers by pitting operational ethics against their humanity. RAs understood and accepted the standard study procedures and the need to maintain their role as researchers. Nevertheless, a majority chose to provide unsolicited information or advice to participants despite the risk of potentially losing their job or causing harm to participants. RAs justified their decision to intervene by the lack and questionable quality of local resources/referrals and the long turnaround from data collection to prevention programming. This article demonstrates how practical exigencies in fulfilling IRB/ethics oversight and designing studies that produce the expected standard of evidence to influence policy and programmatic decisions inadvertently stifle opportunities to translate research into action. We offer specific points of reflection for researchers trained in High Income Country (HIC) perspectives towards decolonizing and improving practices in designing ethical research and establishing reflexive work environments with indigenous researchers. Highlights: Hired data collectors trained to be nonjudgmental, not introduce bias, do no harm. Protocol dictates not to be educator, make referrals, do not provide unsolicited advice. Directives prove inadequate, conflict between research ethics and personal morals. Addressing frontline researcher dilemmas need IRB and study management flexibility. Increased attention to power relations and research work environment necessary.